Long-term adaptation to high doses of morphine causes desensitization of mu-OR- and delta-OR-stimulated G-protein response in forebrain cortex but does not decrease the amount of G-protein alpha subunits - Bourova, Lenka; Vosahlikova, Miroslava; Kagan, Dmytro; Dlouha, Katerina; Novotny, Jiri; Svoboda, Petr (Medical science monitor, 2010)
BACKGROUND: The functional activity of trimeric guanine-nucleotide-binding proteins (G-proteins) represents an essential step in linking and regulation of the opioid receptor (mu-, delta- and kappa-OR)-initiated signaling pathways. Theoretical basis and/or molecular mechanism(s) of opioid tolerance and addiction proceeding in the central nervous system were not studied in the forebrain cortex of mammals with respect to quantitative analysis of opioid-stimulated trimeric G-protein activity. MATERIAL/METHODS: G-protein activity was measured in PercollR-purified plasma membranes (PM) isolated from the frontal brain cortex of control and morphine-treated rats by both high-affinity [32P]GTPase and [35S]GTPgammaS binding assays. Exposition to morphine was performed by intra-muscular application of this drug. Control animals were injected with sterile PBS. RESULTS: Both mu-OR (DAMGO)- and delta-OR (DADLE)-responses were clearly desensitized in PM isolated from morphine-treated rats; kappa-OR (U-69593)- and baclofen (GABAB-R)-stimulated [35S]GTPgammaS binding was unchanged, indicating the specificity of the morphine effect. Under such conditions, the amount of G-protein alpha subunits was unchanged. The order of efficacy DADLE>DAMGO>U-69593 was the same in control and morphine-treated PM. Behavioral tests indicated that morphine-treated animals were fully drug-dependent and developed tolerance to subsequent drug addition. CONCLUSIONS: Prolonged exposure of rats to high doses of morphine results in decrease of the over-all output of OR-stimulated G-protein activity in the forebrain cortex but does not decrease the amount of these regulatory proteins. These data support the view that the mechanism of the long-term adaptation to high doses of morphine is primarily based on desensitization of OR-response preferentially oriented to mu-OR and delta-OR.
Keywords: receptory opiátové delta; buněčná membrána; Receptors, Opioid, delta; Receptors, Opioid, mu; chování zvířat; enkefalin, Ala(2)-MePhe(4)-Gly(5)-; guanosindifosfát; Adaptation, Physiological; abstinenční syndrom; tolerance léku; Dose-Response Relationship, Drug; Baclofen; Morphine; Time Factors; krysa rodu Rattus; proteiny vázající GTP - alfa-podjednotky; zvířata; mozková kůra; Enkephalin, Ala(2)-MePhe(4)-Gly(5)-; potkani Wistar; časové faktory; Cerebral Cortex; GTP-Binding Protein alpha Subunits; Drug Tolerance; Guanosine Diphosphate; Guanosine 5'-O-(3-Thiotriphosphate); Rats, Wistar; Male; fyziologická adaptace; Rats; receptory opiátové mu; vztah mezi dávkou a účinkem léčiva; morfin; guanosin 5'-O-(3-thiotrifosfát); baklofen; Animals; Cell Membrane; mužské pohlaví; Substance Withdrawal Syndrome; Behavior, Animal